The efficiency of Islamic banks in the Southeast Asia (SEA) region - Mohammad Abdul Matin Chowdhury; Razali Bin Haron (Future Business Journal, 2021)
The Islamic banking sector has become a crucial part of the global banking industry. Despite the Islamic banking industry's encouraging growth in the Southeast Asia (SEA) region, prior studies mostly focused on Islamic banks' efficiency in the individual country. To fill the literature gap, this study aims to measure the efficiency and productivity growth of Islamic banks in the SEA region. This study adopted the DEA technique and the Malmquist productivity index to evaluate 31 Islamic banks' performance in SEA from 2014 to 2019. The results evidenced an improvement in efficiency and progress in productivity for the banks in the region. The findings documented better efficiency and gradual progress in productivity for Islamic banks in Indonesia, consistent efficiency for Malaysia, a significant improvement for Brunei; hence, both Thailand and the Philippines Islamic bank depicted a drop-in efficiency for 2019. The findings trigger bank managers to acknowledge the inefficiencies and their sources. Investors and policymakers may find the findings useful in observing the banks' performance; thus, taking effective mechanism and policies to promote competent and sustainable SEA Islamic banks in the long run.
Keywords: 650; DEA; Efficiency; Islamic banking efficiency; Islamic Banks' performance; SEA Islamic banks; The Malmquist productivity index; Total factor productivity (TFP)